Screening of 484 trace organic contaminants in coastal waters around the Liaodong Peninsula, China: Occurrence, distribution, and ecological risk. (December 2020) - Xie, Huaijun; Chen, Jingwen; Huang, Yang; Zhang, Ruohan; Chen, Chang-Er; Li, Xuehua; Kadokami, Kiwao
Abstract: Human activities such as agriculture, aquaculture, and industry can lead to the pollution of coastal waters by trace organic contaminants (TrOCs), and the TrOCs can pose a threat to marine ecosystems. Therefore, it is essential to investigate the occurrence, distribution, and ecological risk of the TrOCs in coastal waters. Previous studies adopting conventional analytical methods have focused on a limited number of targets. Herein, a comprehensive and systematic determination was undertaken to target 484 TrOCs in the waters around the Liaodong Peninsula, China. Eighty-six TrOCs were detected at concentrations of up to 350 ng L −1, and 25 TrOCs were detected at a frequency of >50%. Pesticides were the predominant pollutants, occurring at high concentrations with large detection frequencies. Ecological risks were assessed for single pollutants and mixtures based on the risk quotient and concentration addition modeling, respectively. The detected pesticides posed relatively high risk to aquatic organisms, while pharmaceuticals, consumer products, and other pollutants posed little or no risk. TrOC mixtures posed extremely high risk to aquatic organisms, which represented a significant threat to the marine environment and local communities. The results described here provide useful information that can inform China's "Action Plan for Prevention and Control of Water Pollution". Graphical abstract: Image 1 Highlights: Eighty-six TrOCs were detected in coastal waters around Liaodong Peninsula. Pesticide was predominant pollutant with high concentration and detection frequency. TrOCs mixtures posed extremely high risks to aquatic organisms.